2018
DOI: 10.12659/pjr.901602
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Embolization and Histologic Analysis of Gastric Cancer with Hemorrhagic Shock Using Spherical Embolic Material

Abstract: SummaryBackgroundIn a recent study, it was reported that transcatheter arterial embolization with spherical embolic material for life-threatening hemorrhages in various cancer patients was safe and effective. Calibrated microspheres are able to access distal regions of the target arteries, which results in the disappearance of tumor staining. However, there are few reports on the pathological behavior of EmboSpheres in gastric cancer specimens. In this case, we succeeded in salvage embolization for advanced ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Based on review of current English literature, there has only been one other reported case of a patient presenting with a UGIB secondary to a ruptured SAP in the setting of an underlying gastric cancer [ 12 ]. In traditional bleeding gastric cancers, therapeutic intervention is usually prioritized in the following order: first endoscopic treatment, second transcatheter arterial embolization, and third emergent gastrectomy [ 13 ]. Although upper endoscopy has a high reported success rate in treating actively bleeding inoperable gastric cancers, its therapeutic utility is severely limited by profuse bleeding [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on review of current English literature, there has only been one other reported case of a patient presenting with a UGIB secondary to a ruptured SAP in the setting of an underlying gastric cancer [ 12 ]. In traditional bleeding gastric cancers, therapeutic intervention is usually prioritized in the following order: first endoscopic treatment, second transcatheter arterial embolization, and third emergent gastrectomy [ 13 ]. Although upper endoscopy has a high reported success rate in treating actively bleeding inoperable gastric cancers, its therapeutic utility is severely limited by profuse bleeding [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of lymphadenopathy, omental caking and distant metastasis may also be seen [29]. Angiographic findings include a 'tumor blush' due to neovascularity, pseudoaneurysm formation and active bleeding [30]. Endoscopic findings range from a focal area of mucosal irregularity to a large mass with areas of ulceration and bleeding.…”
Section: Gastric Carcinomamentioning
confidence: 99%